Emergence of Streptococcus pneumoniae serotype 19A (Spn19A) in the pediatric population in Bogotá, Colombia as the main cause of invasive pneumococcal disease after the introduction of PCV10 - Germán Camacho Moreno; Luisa F. Imbachi; Aura L. Leal; Vivian M. Moreno; Jaime A. Patiño; Iván F. Gutiérrez; Sandra Beltrán; Martha I. Álvarez-Olmos; Cristina Mariño; Rocío Barrero; Fabio Espinosa; Nicolás Ramos; et al. (Taylor & Francis Group, 2020)
Introduction: With the use of pneumococcal conjugate vaccines(PCV), the behavior of invasive pneumococcal disease(IPD) has changed relative to serotype distribution. The introduction of these vaccines in national immunization programs has reduced the incidence of IPD, with a marked decrease in the circulation of the serotypes included in the vaccine used in each country. However, the subsequent emergence of other serotypes not included in the vaccine, such 19A in case of PCV7 and PCV10, has been documented. Materials and methods: This was case series study (2008-2017) in pediatric patients admitted to 10 hospitals in Bogota who were diagnosed with IPD. It was conducted during the transitional period of implementing the PCV10 vaccine in Colombia in 2012. Cases of bacteremic pneumococcal pneumonia, meningitis, primary bacteremia and osteoarticular infection were included. A descriptive analysis of the demographic, clinical and laboratory variables of patients with IPD by Spn19A, its trend over time, profiles of antimicrobial susceptibility and clinical outcomes was performed. Results: There were 463 cases of IPD, 315(68%) with known serotypes. The prevalence of IPD by Spn19A was 17.7%(56 cases), tending to increase over time. During 2008-2011, the prevalence was 4.4%, and during 2014-2017, it was 32.4%, The most frequent diagnosis was pneumonia(80.4%). In nonmeningeal isolates, 39.6% were not susceptible to penicillin. An increase in the resistance was observed over time. Conclusion: Spn19A is a prevalent cause of IPD in the pediatric population of the analyzed cohort, with an increasing trend of this serotype during the surveillance period after the introduction of PCV10, being the most common serotype identified in recent years.